Low-Dose Intravenous Soybean Oil Emulsion for Prevention of Cholestasis in Preterm Neonates. (March 2016) - Levit, Orly L.; Calkins, Kara L.; Gibson, L. Caroline; Kelley-Quon, Lorraine; Robinson, Daniel T.; Elashoff, David A.; Grogan, Tristan R.; Li, Ning; Bizzarro, Matthew J.; Ehrenkranz, Richard A.
Background: Premature infants depend on intravenous fat emulsions to supply essential fatty acids and calories. The dose of soybean-based intravenous fat emulsions (S-IFE) has been associated with parenteral nutrition (PN)–associated liver disease. This study's purpose was to determine if low-dose S-IFE is a safe and effective preventive strategy for cholestasis in preterm neonates. Materials and Methods : This is a multicenter randomized controlled trial in infants with a gestational age (GA) ≤29 weeks. Patients <48 hours of life were randomized to receive a low (1 g/kg/d) or control dose (approximately 3 g/kg/d) of S-IFE. The primary outcome was cholestasis, defined as a direct bilirubin ≥15% of the total bilirubin at 28 days of life (DOL) or full enteral feeds, whichever was later, after 14 days of PN. Secondary outcomes included growth, length of hospital stay, death, and major neonatal morbidities. Results : In total, 136 neonates (67 and 69 in the low and control groups, respectively) were enrolled. Baseline characteristics were similar for the 2 groups. When the low group was compared with the control group, there was no difference in the primary outcome (69% vs 63%; 95% confidence interval, −0.1 to 0.22; P = .45). While the low group received less S-IFE and total calories over time compared with the control group ( P < .001 and P = .03, respectively), weight, length, and head circumference at 28 DOL, discharge, and over time were not different ( P > .2 for all). Conclusion : Compared with the control dose, low-dose S-IFE was not associated with a reduction in cholestasis or growth.